Hybrid Governance: Peran Non-State Aktor dalam Resolusi Konflik Perbatasan Indonesia dan Timor Leste di Oepoli - Sabaat, Yeftha Y; Jacob, Ananias R.P.; Ndoda, Philips Y.N.; Triadmaja, Stefanus (Jurnal Ragam Pengabdian, 2025)
This study examines the role of non-state actors in resolving the border conflict between Indonesia and Timor Leste. Non-state actors have significant influence in border communities, through social, political, and economic networks. They often act as mediators in conflict negotiations, bridging the interests of local communities and the governments of both countries. This study focuses on: first, what is the role of non-state actors in the process of resolving the Indonesia-Timor Leste border conflict? Second, what is the relationship between state and non-state actors in the context of conflict resolution? The theoretical framework used in this study is conflict resolution theory to examine the relationship between state and non-state actors in managing border conflicts, both in resolution efforts and efforts to maintain peace on the border. This study uses a qualitative method by utilizing a case study of the role of Non-State Actors in resolving the Indonesia-Timor Leste border conflict in Oepoli. This study found that conflict resolution efforts by non-state actors actually have a significant contribution and are more accepted by the conflicting communities/actors. Conflict resolution efforts by non-state actors also contribute to maintaining peace and represent a new approach to conflict resolution on the border.